Inequalities in health in a municipality of Serbia - Simović Tatjana; Radojlović Jasmina; Memić Mensur (Vojnosanitetski Pregled)
Background/Aim. A consistent association between socioeconomic determinants and health related variables has been found in many European countries. The aims of this study were: to analyze the association of socioeconomic factors with self-perceived health and utilization of health services as well as to suggest some interventions to overcome the existing problems. Methods. Hybrid study was pefrormed. The two cross-sectional studies were conducted on quota samples (1999 and 2015) in Kruševac Municipality. The questionnaire was used as the investigation instrument for 196 interviewees in 1999 and 226 interviewees in 2015. Results. In the reporting period, there were the following results: a significant increase in people who did not have a steady income (χ2 = 22.800; df = 4; р < 0.01), a decrease in the number of people who perceived their own health as “well“ and “very well“, a significant increase (6.1%) in people who did not visit anyone when disease occurred, a decrease of 13.2% in number of people who, at least once, visited the general practitioner and an increase in the number of people who visited private health care sector. The findings revealed inequalities in self-perceived health depending on socioeconomic position, in particular educational and employment status (χ2 = 11.293; df = 4; p < 0.05). There are two major ways in which unemployment affects health: lack of income and ability to meet daily needs and emotional stress related to the meaning of the work, uncertain future, loss of self-esteem, and identity. Conclusion. Equality is a key value in the assessment of the effects on health. It is necessary to conduct effective interventions for overcoming the consequences in society that would be focused on a specific target group in one territory.